Medically assisted reproduction and parent–child relationships during adolescence: evidence from the UK Millennium Cohort Study. Issue 3 (4th January 2021) - Goisis, Alice; Palma, Maria
Abstract: STUDY QUESTION: Do the parent–child relationships of adolescents born after medically assisted reproduction (MAR) using the parents' own gametes differ from those of adolescents born after natural conception (NC)? SUMMARY ANSWER: MAR and NC families have similar parent–child relationships in terms of closeness and conflict frequency, except that MAR mothers report being closer to their children than NC mothers. WHAT IS KNOWN ALREADY: Prior work on parent–child relationships during childhood has reported mixed findings. While some studies have documented no differences between MAR and NC families, others have shown that MAR families have greater levels of warmth and positive feelings than NC families. Evidence on parent–child relationships during the adolescent period is generally positive but is limited because of the small number of existing studies and the reliance on small samples. STUDY DESIGN, SIZE, DURATION: This work is based on the UK Millennium Cohort Study, whose study members were born in 2000–2002. The analyses focused on Sweep 6 which was collected when cohort members were around 14 years old. We also relied on variables collected in Sweep 1, when cohort members were aged around 9 months, to account for characteristics that could confound or mediate the relationship between MAR and our outcomes. The attrition rate between Sweeps 1 and 6 was 36.7%. PARTICIPANTS/MATERIALS, SETTING, METHODS: The final sample consisted of 10 233 cohort members, 320 of whom were conceived with the help of MAR (3.1%). A total of six dependent variables were used to measure, when the cohort members were around 14 years old, levels of parent–child closeness and conflict, reported separately by the mother, the father and the cohort member. Linear models were used to analyse the association between parent–child relationships before and after adjustment for socio-demographic characteristics and mental health. MAIN RESULTS AND THE ROLE OF CHANCE: Sweep 6 achieved a response rate of 76.3% of the eligible sample. The results show that, on average, MAR and NC families had similar parent–child relationships in terms of closeness and conflict frequency. The only difference was that MAR mothers reported being closer to their children than NC mothers both before ( β  = 0.149, P  < 0.05) and after ( β  = 0.102, P  < 0.1) adjustment for family socio-demographic characteristics and mental health. LIMITATIONS, REASONS FOR CAUTION: The outcome variables are self-reported by each of the respondents and could be subject to social desirability bias. Second, some parents may have not reported they conceived through donor insemination, which could result in the analytical sample including a small subset of children who were not genetically related to their parents. Third, the data did not include information about whether the children were aware of their conception mode, since the Millennium Cohort Study did not collect information on MAR disclosure. Moreover, they did not allow us to study other aspects of parent–child relationships. Finally, as we observed parent–child relationships at only one moment in time; we were unable to test whether they changed over time. WIDER IMPLICATIONS OF THE FINDINGS: The results suggest that the difficulties and the stress parents underwent to conceive through MAR did not translate into more difficult parent–child relationships during adolescence. Given the increasing number of children conceived via MAR, the finding that MAR and NC families had similar parent–child relationships in terms of closeness and conflict frequency is reassuring. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by European Research Council agreement n. 803959 (MARTE to A.G.). The authors declare no competing interests. TRIAL REGISTRATION NUMBER: n/a